Ketoasidosis Diabetikum - Suherna Musfira S; Mawaddah Fitria (Pusat Riset dan Inovasi Nasional, 2024)
Diabetic ketoacidosis (DKA) is a serious, acute complication of diabetes mellitus and is an emergency that must be treated immediately. DKA requires fast and precise management, considering the high mortality rate. DKA is a state of metabolic decompensation characterized by the triad of hyperglycemia, metabolic acidosis, and ketosis and is an emergency in the field of endocrinology that is most frequently encountered in daily practice. Data in America is that more than 100,000 patients are treated per year for DKA (3). . Although there is no community data in Indonesia, it seems that the incidence of DKA in Indonesia is not as high as in western countries, considering the low prevalence of type 1 DM. Reports of the incidence of DKA in Indonesia generally come from hospital data and especially in type II DM patients (4). Successful management of DKA requires correction of dehydration, hyperglycemia, acidosis and electrolyte abnormalities, identification of comorbid precipitating factors, and most importantly continuous patient monitoring.